A wasted hand: Case with uncommon neurological and radiological features caused by a cervical band. Issue 1 (January 1975) - Bergquist, E.; Hugosson, R.; Westerberg, C. -E.
Abstract : The symptomatology in the thoracic outlet syndrome is well known. A patient is reported in whom the finding of a unilateral pulse deficit was the alerting sign that led to the correct diagnosis. Angiography, performed with injections during different respiratory phases, visualized the pathogenetic mechanism underlying some of the clinical findings.